2017
DOI: 10.1007/s10096-017-2998-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of severe hematological abnormalities in the outcome of hospitalized patients with influenza virus infection

Abstract: Although hematological abnormalities have been described among patients with influenza virus infection, little is known about their impact on the outcome of the patients. The aim of this study was to assess the frequency and clinical impact of severe hematological abnormalities in patients with confirmed influenza virus infection. This was an observational retrospective study including all adult patients with diagnosis of influenza virus infection hospitalized from January to May 2016 in our institution. Influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…On the contrary, other authors have found that high influenza viral load is associated with a longer duration of hospital stay in adults with viral acute respiratory illness [5]. On this basis, we decided to analyze the role of influenza viral load in the outcome of the patients included in the same cohort of our previous paper [1].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the contrary, other authors have found that high influenza viral load is associated with a longer duration of hospital stay in adults with viral acute respiratory illness [5]. On this basis, we decided to analyze the role of influenza viral load in the outcome of the patients included in the same cohort of our previous paper [1].…”
Section: Introductionmentioning
confidence: 97%
“…We recently reported the potential role of severe hematological abnormalities as prognostic markers in hospitalized patients with influenza virus infection [1]. However, the role of viral load in the clinical outcome and/or in the appearance of some severe hematological abnormalities was not evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Hemophagocytic lymphohistiocytosis in influenza is caused by an increase in proinflammatory cytokines, which increases hemophagocytic macrophage proliferation and activation in the reticuloendothelial system. As a result, the number of leukocytes and platelets decreases rapidly [20,21]. Lalueza et al [21] studied the effects of severe hematological abnormalities in patients admitted to hospital for influenza virus infection; they pointed out that these hematological abnormalities are especially common at the onset of the disease and cause hospitalization and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the number of leukocytes and platelets decreases rapidly [20,21]. Lalueza et al [21] studied the effects of severe hematological abnormalities in patients admitted to hospital for influenza virus infection; they pointed out that these hematological abnormalities are especially common at the onset of the disease and cause hospitalization and poor prognosis. In a study of hematological findings of influenza, when H1N1 infection was diagnosed, 8 (25.8%) patients had leukopenia and 6 patients (19.4%) had thrombocytopenia, It has been reported that H1N1 infection can lead to various hematological findings including cytopenia and hemophagocytosis [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation